THE RELATIONSHIP BETWEEN NURSE CARING BEHAVIOR AND ANXIETY LEVELS AMONG COVID-19 PATIENTS - Erik Kusuma; Ayu Dewi Nastiti; Dwining Handayani; R.A. Helda Puspitasari (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Nahdlatul Ulama Surabaya, 2021)
Background: Covid-19 patients who undergoing treatment in isolation rooms experience anxiety problems due to loss of contact with their surrounding. Caring behavior in providing nursing services provides comfort and tranquillity for patients. Objective: This study aimed to determine the relationship between nurses' caring behavior with the anxiety level of Covid-19 patients undergoing treatment in the isolation rooms. Methods: This study used a cross-sectional design. The sample in this study was COVID-19 patients undergoing treatment in the Isolation Room as many as 30 people. The respondents were selected using a consecutive sampling technique. The anxiety levels were measured using the State-Anxiety Inventory (S-AI) questionnaire. The data were analyzed using the Gamma and Somers'd correlation test. Results: The results showed that the better caring behaviour by nurses the lesser the anxiety level of patients. Gamma statistical test results obtained a p-value of 0.000 <0.05, which means that there was a significant relationship between nurses' caring behaviour and the anxiety level of Covid-19 patients in the Isolation Room. Conclusions: The caring behaviour of nurses in Covid-19 patients was shown by the presence of caring, empathy, compassion, and good communication so that a therapeutic relationship is established between patients and nurses. Therefore, the patient feels safe, comfortable, and has less anxiety.